SELF-ORGANIZING MAPS-BASED METHOD FOR THE ANALYSIS OF HEMARTHROSIS DATA IN HAEMOPHILIC PATIENTS - PÉREZ-ALENDA, SOFÍA; CARRASCO, JUAN J.; RODRÍGUEZ, MARTA AGUILAR-; SORIA-OLIVAS, EMILIO; MARTÍNEZ, JOSE MARÍA MARTÍNEZ-; BONANAD-BOIX, SANTIAGO; QUEROL, FELIPE (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Joint bleeding are the most common injuries in hemophilia and if not treated properly canlead to disabling arthropathies from an early age. In order to ensure a good quality of life related tohealth in hemophilic patients is necessary a continuous monitoring of these injuries in addition totreatments that involve a very high cost to the health system. In this work, a database of hemofiliapatients is analyzed using Self-Organizing Maps (SOM). All variables are depicted together, so that it is possible to obtain the relationships between them, identifying possible clusters in data, and infervarious characteristics of the tested population. Results obtained show that it is possible to obtain allthis information in an intuitive and visual way, facilitating to the specialists the task of analysis.